Distinct virulence ranges for infection of mice by Bordetella pertussis revealed by engineering of the sensor-kinase BvgS. - Elodie Lesne; Loic Coutte; Luis Solans; Stephanie Slupek; Anne-Sophie Debrie; Véronique Dhennin; Philippe Froguel; David Hot; Camille Locht; Rudy Antoine; Françoise Jacob-Dubuisson (PLoS ONE, 2018)
The whooping cough agent Bordetella pertussis coordinately regulates the expression of its virulence factors with the two-component system BvgAS. In laboratory conditions, specific chemical modulators are used to trigger phenotypic modulation of B. pertussis from its default virulent Bvg+ phase to avirulent Bvg- or intermediate Bvgi phases, in which no virulence factors or only a subset of them are produced, respectively. Whether phenotypic modulation occurs in the host remains unknown. In this work, recombinant B. pertussis strains harboring BvgS variants were tested in a mouse model of infection and analyzed using transcriptomic approaches. Recombinant BP-BvgΔ65, which is in the Bvgi phase by default and can be up-modulated to the Bvg+ phase in vitro, could colonize the mouse nose but was rapidly cleared from the lungs, while Bvg+-phase strains colonized both organs for up to four weeks. These results indicated that phenotypic modulation, which might have restored the full virulence capability of BP-BvgΔ65, does not occur in mice or is temporally or spatially restricted and has no effect in those conditions. Transcriptomic analyses of this and other recombinant Bvgi and Bvg+-phase strains revealed that two distinct ranges of virulence gene expression allow colonization of the mouse nose and lungs, respectively. We also showed that a recombinant strain expressing moderately lower levels of the virulence genes than its wild type parent was as efficient at colonizing both organs. Altogether, genetic modifications of BvgS generate a range of phenotypic phases, which are useful tools to decipher host-pathogen interactions.